Peran Perpustakaan dalam Peningkatan Mutu Pendidikan di UIN Sunan Ampel Surabaya - Supriyatno, Hary (Balai Diklat Keagamaan Surabaya, 2020)
This study aims to determine the role of libraries in improving the quality of education at the State Islamic University of Sunan Ampel Surabaya. The approach used in this research is qualitative with the case study method, which is to reveal and understand certain phenomena that occur in society in depth based on existing data. (Prihatsanti, 2018: 127-128). The results of the research analysis found that with sufficient resources owned, UINSA Libraries are able to play a role in at least four of the nine higher education accreditation criteria, namely facilities and infrastructure, education, research, and community service. The quality of these resources can be proven by the achievement of the A accreditation status achieved by the Sunan Ampel UIN Library since 2015.